Frequency of Procedural Errors during Root Canal Treatment Performed by House Officers in Private Teaching Dental Hospital - Ali, Syed Abrar; Hussain, Mehmood; Shahzad, Muhammad; Nafees, Hina (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To determine the procedural errors produced during the conventional root canal treatment and to find out the association of errors with particular teeth. METHODOLOGY: This descriptive observational type study was conducted in Private Teaching Dental Hospital. A total 200 root canal treated teeth were assessed through peri-apical radiographs using non-probability convenient sampling technique. The data was collected from patient record files retrospectively performed by house officers in the duration of 1 year in department of Operative Dentistry. Data analysis was done by using SPSS version 22. Frequency and percentage statistics were used. RESULTS: Out of sample size of 200 patients, 110 (55%) were females and 90 (45%) were males with age range from 10 to 50 years. The most frequently treated tooth was the mandibular right first molar (29.5%) followed by permanent maxillary right first molar(26%). The most frequent tooth to possess an error was the mandibular right first molar (59%), followed by maxillary right first molar (52%). Instrument separation was the most common procedural error 148 (74%), followed by ledge 25 (12.5 %). CONCLUSION: The results concluded that instrument separation was the most frequent procedural error and the most frequent tooth to possess an error was the mandibular right first molar.